Proceedings (110) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
First meeting of the LOOP Coordinating Committee CARINET is the proceedings of a meeting held from 4-5 November 1996, Port of Spain, Trinidad edited by St Clair Forde and Ronald Barrow 134ppCARINET, Gordon Street, Curepe, Trinidad & Tobago, WI